Conformational Epitopes Recognized by Protective Anti-Neisserial Surface Protein A Antibodies - Hou, Victor C. (American Society for Microbiology, 2003)
NspA is a conserved membrane protein that elicits protective antibody responses in mice against Neisseria meningitidis. A recent crystallographic study showed that NspA adopts an eight-stranded β-barrel structure when reconstituted in detergent. In order to define the segments of NspA-containing epitopes recognized by protective murine anti-NspA antibodies, we studied the binding of two bactericidal and protective anti-NspA monoclonal antibodies (MAbs), AL12 and 14C7. Neither MAb binds to overlapping synthetic peptides (10-mers, 12-mers, and cyclic 12-mers) corresponding to the entire mature sequence of NspA, or to denatured recombinant NspA (rNspA), although binding to the protein can be restored by refolding in liposomes. Based on the ability of the two MAbs to bind to Escherichia coli microvesicles prepared from a set of rNspA variants created by site-specific mutagenesis, the most important contacts between the MAbs and NspA appear to be located within the LGG segment of loop 3. The conformation of loop 2 also appears to be an important determinant, as particular combinations of residues in this segment resulted in loss of antibody binding. Thus, the two anti-NspA MAbs recognize discontinuous conformational epitopes that result from the close proximity of loops 2 and 3 in the three-dimensional structure of NspA. The data suggest that optimally immunogenic vaccines using rNspA will require formulations that permit proper folding of the protein.